2020
DOI: 10.1177/2151459320964030
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Pre-Operative Medical Co-Morbidities on Rehabilitation Outcomes Following Surgery for Hip Fracture Management in Geriatric Populations

Abstract: Introduction: As a result of increasing longevity, we are seeing more elderly patients with complex medical co-morbidities who sustain hip fractures requiring surgical management. The aim of this study is to understand and analyze the effect of preoperative medical comorbidities and associated low physiological reserve status on functional rehabilitation outcomes following surgical management of hip fractures. Materials and methods: This study conducted a retrospective analysis of 73 patients who fulfilled the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
4
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 15 publications
0
4
1
Order By: Relevance
“…To the best of our knowledge, this is the first study to explore the relationship between DEMMI scoring and sarcopenia. While previous research has indicated that the DEMMI score is a useful tool for determining patient outcomes, 12–14 we did not see an association with sarcopenia. This may possibly be due to the skewed DEMMI scores (median DEMMI = 100) seen in our study, reflecting a high level of pre‐operative mobility.…”
Section: Discussioncontrasting
confidence: 97%
See 2 more Smart Citations
“…To the best of our knowledge, this is the first study to explore the relationship between DEMMI scoring and sarcopenia. While previous research has indicated that the DEMMI score is a useful tool for determining patient outcomes, 12–14 we did not see an association with sarcopenia. This may possibly be due to the skewed DEMMI scores (median DEMMI = 100) seen in our study, reflecting a high level of pre‐operative mobility.…”
Section: Discussioncontrasting
confidence: 97%
“…12 It has been increasingly used for predicting functional recovery after surgery. 13,14 Despite a close relationship between mobility scores and sarcopenia, the association between DEMMI score and sarcopenia has not been established. 10 Due to its ease of use, DEMMI may serve an additional function to predict sarcopenia.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…7,18 Individuals suffering from a higher number of comorbidities have a poorer functional recovery and prolonged postoperative rehabilitation, with associated financial implications. 23 Such changes will necessitate a considerable increase in resource across health and social care services, with previous estimates anticipating an additional £1.4 billion annually in the UK simply to meet demand. 24 Considering relative comparative hip fracture volumes across England and Scotland, our estimates would suggest a more conservative additional total UK cost of approximately £300 million, although this does not consider increased infrastructure (beds), additional staffing, and theatre resource, as well as recent high inflation.…”
Section: Discussionmentioning
confidence: 99%
“…Generally, the main treatment for hip fractures is surgery, however elderly patients with hip fractures often have many basic diseases when they are admitted to the hospital. George et al [ 3 ] found that when elderly patients with hip fractures had a variety of other diseases, the risk of postoperative morbidity and mortality increased. Their data showed that 20% of the patients had postoperative complications, and the 30-day death rate of such patients was 9%.…”
Section: Introductionmentioning
confidence: 99%